2015
DOI: 10.1177/1934578x1501001152
|View full text |Cite
|
Sign up to set email alerts
|

Potential Skin Regeneration Activity and Chemical Composition of Absolute from Pueraria thunbergiana Flower

Abstract: The flower of Pueraria thunbergiana BENTH (PTBF) contains isoflavonoids and essential oil components. It has many biological and pharmacological activities, including anti-diabetes, anti-oxidant, and weight loss. However, its effect on skin regeneration remains unknown. In the present study, we isolated the absolute from PTBF through solvent extraction and determined the role of the absolute on skin regeneration-associated responses in human epidermal-keratinocytes (HaCats). The PTBF absolute, which contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…To confirm the proliferative and migratory effects of PFFA in keratinocytes, we performed a collagen sprout outgrowth assay that can provide simultaneous measurement of HaCaT cell proliferation and migration. [27,28] Treatment with 1 to 200 μg/mL of PFFA significantly induced sprout outgrowth at 50 μg/mL (761.95 � 65.44 % of untreated control) and 100 μg/mL (588.55 � 17.49 % of untreated control) (n = 3; Figure 3). Therefore, these sprout outgrowth results support our results regarding the stimulation of cell proliferation and migration by PFFA mentioned above.…”
Section: Effect Of Pffa On Hacat Cell Sprout Outgrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the proliferative and migratory effects of PFFA in keratinocytes, we performed a collagen sprout outgrowth assay that can provide simultaneous measurement of HaCaT cell proliferation and migration. [27,28] Treatment with 1 to 200 μg/mL of PFFA significantly induced sprout outgrowth at 50 μg/mL (761.95 � 65.44 % of untreated control) and 100 μg/mL (588.55 � 17.49 % of untreated control) (n = 3; Figure 3). Therefore, these sprout outgrowth results support our results regarding the stimulation of cell proliferation and migration by PFFA mentioned above.…”
Section: Effect Of Pffa On Hacat Cell Sprout Outgrowthmentioning
confidence: 99%
“…[19 -23] Several recent studies have demonstrated that plants and their extracts can improve skin wound and barrier repair functions. [24][25][26][27][28] However, PF flower absolute has not been previously investigated in this context.…”
Section: Introductionmentioning
confidence: 99%
“…This promotes skin proinflammatory activity and epithelialization, resulting in skin regeneration and wound healing. Kim and his Korean team conducted their research on isoflavonoids from the flower of kudzu plant, whose skin-regenerating effect was still unknown at that time [36]. They investigated the skin-regenerative potential of isoflavonoids in human epidermal keratinocytes (HaCats) and found that it induced type I and IV collagen synthesis in HaCats, and the treatment with these isoflavonoids increased sprout outgrowth in HaCats [36].…”
Section: Skin Regeneration Activitymentioning
confidence: 99%
“…Kim and his Korean team conducted their research on isoflavonoids from the flower of kudzu plant, whose skin-regenerating effect was still unknown at that time [36]. They investigated the skin-regenerative potential of isoflavonoids in human epidermal keratinocytes (HaCats) and found that it induced type I and IV collagen synthesis in HaCats, and the treatment with these isoflavonoids increased sprout outgrowth in HaCats [36]. The results suggest that these phytochemical compounds may participate in skin regeneration by promoting migration, proliferation, and collagen synthesis.…”
Section: Skin Regeneration Activitymentioning
confidence: 99%
“…The constituent parts of this plant contain isoflavones, such as puerarin, daidzin, genistin, daidzein, and genistein . The extract of P. lobata has shown a wide range of beneficial effects, including antioxidant/anti‐diabetic effects, weight loss, collagen synthesis, anti‐melanogenic effects, anti‐aging/moisturizing effects, and procollagen formation . Thus, fermentation of the P. lobata extract (FPE) with the equol‐producing aerobic strain L. paracasei JS1 was expected to increase the efficacy of the extract, because equol and its precursors are abundant with the P. lobata extract (PE) and equol precursors might be bioconverted to equol during fermentation.…”
Section: Introductionmentioning
confidence: 99%